2018
DOI: 10.1159/000493558
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Treatment Protocols Using Systemic and Intratympanic Steroids with and without Hyperbaric Oxygen Therapy in Patients with Severe to Profound Idiopathic Sudden Sensorineural Hearing Loss: A Randomized Controlled Trial

Abstract: Objectives: This study aimed to investigate the efficacy of simultaneous steroid and hyperbaric oxygen therapy (HBOT) in patients with severe to profound idiopathic sudden sensorineural hearing loss (ISSNHL), which has a poor prognosis. Methods: Sixty patients diagnosed with severe to profound ISSNHL (≥70 dB HL) were randomly divided into two groups in a prospective controlled trial: an oral steroid + intratympanic steroid injection (ITSI) group (control group) and an oral steroid + ITSI + HBOT group (study gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 31 publications
5
47
0
1
Order By: Relevance
“…In a recent study, comparing oral+IT steroid and oral+IT steroid+HBO therapies in ISSHL patients with severe and profound hearing loss (>70 dB), the addition of HBO to steroid combination therapy did not improve the mean PTA values. However, in the same study, they reported that the addition of HBO was beneficial for improving low-frequency hearing and word discrimination scores [ 21 ]. In our study, when the patients with severe and profound hearing loss (>60 dB) were evaluated separately, there was no significant difference between the two treatment groups in terms of both hearing gain and recovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, comparing oral+IT steroid and oral+IT steroid+HBO therapies in ISSHL patients with severe and profound hearing loss (>70 dB), the addition of HBO to steroid combination therapy did not improve the mean PTA values. However, in the same study, they reported that the addition of HBO was beneficial for improving low-frequency hearing and word discrimination scores [ 21 ]. In our study, when the patients with severe and profound hearing loss (>60 dB) were evaluated separately, there was no significant difference between the two treatment groups in terms of both hearing gain and recovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…Sudden sensorineural hearing loss (SSNHL) is defined as an abrupt hearing deterioration of 30 dB or greater over 3 contiguous frequencies occurring within 72 hours. 1 Although the etiology of SSNHL still remains unclear and is therefore classified as idiopathic,4 possible underlying causes have been proposed: Viral disease, vascular compromise, immune-mediated processes, and cochlear membrane rupture. 2,3 Among these causes of SSNHL, vascular compromise or damage could include thrombotic vascular events, increased plasma viscosity, and vasospasm, resulting in minor cochlear infarction that resembles an acute myocardial infarction and cerebral stroke.…”
Section: Introductionmentioning
confidence: 99%
“…After assessing the remaining 99 full-text articles, 41 studies were excluded for the following reasons: foreign language (n = 3), case reports (n = 3), review or meta-analysis (n = 10), and no mention of complications (n = 25). Finally, 58 studies 1-5,9-61 were included in the systemic review and meta-analysis including 25 randomized controlled trials, 10 prospective studies, and 22 retrospective case-controlled studies ( Table 1 ). A total of 2824 patients served as participants in the meta-analysis wherein 2567 received ITSI via TC (54 articles) and 257 received ITSI via VT (4 articles).…”
Section: Resultsmentioning
confidence: 99%